X+7-5x=-13

Simple and best practice solution for X+7-5x=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+7-5x=-13 equation:


Simplifying
X + 7 + -5x = -13

Reorder the terms:
7 + X + -5x = -13

Solving
7 + X + -5x = -13

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + X + -7 + -5x = -13 + -7

Reorder the terms:
7 + -7 + X + -5x = -13 + -7

Combine like terms: 7 + -7 = 0
0 + X + -5x = -13 + -7
X + -5x = -13 + -7

Combine like terms: -13 + -7 = -20
X + -5x = -20

Add '5x' to each side of the equation.
X + -5x + 5x = -20 + 5x

Combine like terms: -5x + 5x = 0
X + 0 = -20 + 5x
X = -20 + 5x

Simplifying
X = -20 + 5x

See similar equations:

| F^2-18f+81=0 | | 5(4+m)=3(m+2) | | 3x-2[3x+0.5]=1 | | 7y=21+2x | | 3/4b-14=5 | | 10/8+(-3) | | 3x-9(x+4)=-58 | | 23=50n | | -4/7x-12=-40 | | 7x-6(x+4)=29 | | 3x-9(x+4)=-114 | | 4z^2+96z-100=0 | | 6-3x=5(2-x)+2x | | X-(2/100X)=11298.50 | | 3x*2+20x+36=4 | | 4y-7(y-5)=38 | | 3(y+5)=-y+7 | | 6x^2+5x-4/3x-2 | | 5x+-3(x+-6)=2 | | gh+f=k | | 8/7x+1/3=7/12 | | 10x^2-3x-36=0 | | 8/15=x/12 | | 2/3(12x-6)=-28 | | 5x-3(z-6)=2 | | x*2+4x=-1 | | 26=6x-21 | | 2/15=x/12 | | -36-4x=32 | | 6x+10=3x+6 | | 1/3(6x-3)=-28 | | 9x^2+13x-90=0 |

Equations solver categories